Sustainable improvement of HbA1c and satisfaction with diabetes care after adding telemedicine in patients on adaptable insulin regimens: Results of the TeleDiabetes randomized controlled trial. (March 2020) - Buysse, Heidi; Coremans, Peter; Pouwer, Frans; Ruige, Johannes
This 2-year study evaluates whether tele-education adds to improvement and maintenance of good glycemic control and patient satisfaction. Adult patients were randomly assigned to study, getting immediate access to tele-education, or control group, getting this surplus education after 3 months. At several moments, clinical data were retrieved and patients completed questionnaires. Multivariate analyses of covariance and repeated measures analysis of variance were conducted. Implementation of tele-education in between face-to-face contacts improved glycemic control for both groups, which was maintained over a 2-year period. Tele-education did not have an influence on glucose measurements or on hypoglycemic events. Patients were satisfied with this tele-educational tool and appreciated use of personal messages. Further research should focus on the possible influence of "life changes" and influence on "need for more tele-educational feedback, " and consequently on the provision of (mobile) platforms adaptable to patient's (changing life) situations.